The Effect of Science Learning Integrated with Local Potential of Wood Carving and Pottery Towards the Junior High School Students Critical Thinking Skills - Dewi, I. P. M.; Suryadarma, I. G. P.; Wilujeng, I.; Wahyuningsih, S. (Jurnal Pendidikan IPA Indonesia, 2017)
This study aims to analyze the influence of science learning integrated with the local potential of wood carving and pottery to the critical thinking skill of class VIII SMP students. This research is a quasi-experimental research (quasi-experiment). The research design uses pretest-posttest control group design. The population in this study is the students of class VIII MTs Negeri Piyungan, while the sample is the students of class VIII A and VIII B MTs Negeri Piyungan. The technique of collecting data in this research is in the form of test. The data collection instrument is a critical thinking skill descriptive test. The data were analyzed using ANOVA test. The results of this study indicate that the learning of science integrated with the local potency of wood carving and pottery have an effect on critical thinking skill of class VIII SMP student. This effect is indicated by a significance of 0.008 (significance <0.05).